2017
DOI: 10.4236/cn.2017.91002
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Model of Job Involvement, Job Satisfaction and Organizational Commitment: A Structural Analysis in Jordan’s Banking Sector

Abstract: The purpose of this research is to investigate the interrelationships among the three behavioural constructs of job involvement, job satisfaction and organizational commitment. Accordingly, a structural model is developed to delineate the interactions among these constructs and explore the mediating effect of job satisfaction on the relationship between job involvement and organizational commitment. A questionnaire-based survey was designed to test the aforementioned model based on a dataset of 315 employees w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 84 publications
4
44
2
1
Order By: Relevance
“…Engagement is the attachment of members of organization to the roles of work assigned to them, and in engagement, people physically, cognitively and emotionally make use of and articulate themselves during role performances (Abdallah et al, 2017). Engagement can likewise be described as an unrelenting and positive affective-motivational state of accomplishment (Field and Buitendach, 2011).…”
Section: Employee Engagementmentioning
confidence: 99%
See 2 more Smart Citations
“…Engagement is the attachment of members of organization to the roles of work assigned to them, and in engagement, people physically, cognitively and emotionally make use of and articulate themselves during role performances (Abdallah et al, 2017). Engagement can likewise be described as an unrelenting and positive affective-motivational state of accomplishment (Field and Buitendach, 2011).…”
Section: Employee Engagementmentioning
confidence: 99%
“…Job satisfaction is the main priority for all organizations in establishing their policy (Yücel, 2012, ), and as a concept that has linkage to the humanitarian and utilitarian viewpoints, it is worth the scrutiny. The humanitarian viewpoint is postulates that employee satisfaction level is linked to the degree to which employees are receiving fair and apposite treatment in the organization (Abdallah et al ,2017), whereas the utilitarian viewpoint indicated that employee satisfaction contributes to behaviors impacting the operation of the organization (Yücel, 2012). Job satisfaction is also viewed as a quantifiable depiction of an emotion related response towards certain job; in other words, the person performing the job feels satisfied with it (Al-dalahmeh et al, 2018;Anitha, 2014).…”
Section: Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this research underlines the effect of insight orientation and workplace relational civility (others with me) in mediating the relationship between predisposition to change and job satisfaction. This adds an additional piece to a growing body of research that analyzes the employees' attitudes and dispositions towards one's job [106] which in turn will inevitably influence the organizational outcomes [107]. In this perspective, therefore, the present study provides a further contribution to increase the effectiveness of preventive intervening in favor of positive results for greater well-being of subjects and organizations.…”
Section: Discussionmentioning
confidence: 85%
“…This means that JI directly influences AC. Previous research similarly concludes that employees' high JI will make employees have a deep emotional attachment (AC) to stay in the organization (36)(37)(38). People who are not involved in their jobs and who think that their jobs are not an important aspect of their life, psychologically, what can occur is dissatisfaction with their superior as a whole, and it results in low AC in employees (22).…”
Section: B)mentioning
confidence: 95%